Optimization of the upper completion assembly by using redundant pump exemplified by the well in the Prirazlomnoye field, Pechora Sea - Andreev, Andrei (University of Stavanger, Norway, 2017)
Master's thesis in Offshore Technology: Subsea and Marine technology Nowadays development of Russian offshore oil and gas fields is relevant and perspective. A lot of Russian and foreign oil and gas companies tend to get an experience in offshore field development by establishing pilot projects even in the Arctic. Although oil price is rather low, deal with offshore projects more attractive compare to an onshore, because of higher reservoir productivity of offshore oil fields. It allows us to open new horizons and gather required experience for the future projects. Sometimes, one oil platform derives more oil than subsidiary oil company may. Presence characterized by high leasehold price for an oil platform, marine vessels, and equipment. Therefore, oil companies aim at an operating cost reduction, ensuring the reliability and integrity of all platform systems, and their downtime reduction. The problem, which will be considered in the thesis, is an artificial oil production system failure (namely upper completion and ESP). Sometimes oil platforms have one drilling rig and sometimes even do not have and in a case of failure of any main module of the upper completion, the oil production stops and it will be continued only after replacement of broken equipment and pulling a new one, But what we have in a case while drilling? We cannot replace the upper completion till drilling of the well is done or we have to stop drilling in order to renew our well with the broken upper completion. Anyway, in both cases company loses money and time. In the thesis will be considered the upper completion assembly with two ESP in series, for ensuring work of one of them in case of another failure (pumps work alternately, for their guaranteed start). With the help of the special program required pumps and their operational characteristics will be chosen. This concept may reduce well downtime, but only in case of trouble-free operation of other modules of the upper completions, that also may stop production (circulation valve, ...